REGRESI NONPARAMETRIK KERNEL ADJUSTED - , NOVITA EKA CHANDRA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Nadaraya watsonâs kernel adjusted regression estimator is an estimator that whose kernel is taken from the family of scale-location associated with the classical kernel density estimator. Based on these estimator, it can be obtained optimal bandwith and scale parameter. This estimator gives a better estimation results compared with Naradaya Watsonâs clasical kernel regression estimator. This is proven by the small grade MSE which is given by this estimator.